Experimental Quantum Message Authentication with Single Qubit Unitary Operation - Kang, Min-Sung; Kim, Yong-Su; Choi, Ji-Woong; Yang, Hyung-Jin; Han, Sang-Wook (MDPI, 2021)
We have developed a quantum message authentication protocol that provides authentication and integrity of an original message using single qubit unitary operations. Our protocol mainly consists of two parts: quantum encryption and a correspondence check. The quantum encryption part is implemented using linear combinations of wave plates, and the correspondence check is performed using Hong-Ou-Mandel interference. By analyzing the coincidence counts of the Hong-Ou-Mandel interference, we have successfully proven the proposed protocol experimentally, and also showed its robustness against an existential forgery.
Keywords: SIGNATURE SCHEME; KEY DISTRIBUTION; CRYPTOGRAPHY; SECURITY